Analisis SWOT: Strategi Pengembangan Berkelanjutan Desa Wisata Jatiluwih, Tabanan, Bali - I Nyoman Subrata; I Made Bayu Wisnawa; I Ketut Sutapa (Widya Manajemen, 2026)
Sustainable tourism is a tourism management concept aimed at generating long-term benefits without causing harm to the environment or local socio-cultural life. This concept is implemented through the management of tourism villages, which actively involve local communities in developing tourist destinations. One of the World’s Best Tourism Villages in 2024 is Jatiluwih Tourism Village, located in Bali. The purpose of this study is to identify and understand the role of local community involvement in developing Jatiluwih Tourism Village to create sustainable tourism; to analyze the impacts of its development on the economic sustainability of local communities, social improvement, cultural preservation, and environmental conservation; and to determine appropriate strategies for sustainable tourism development in the village. This study employs a qualitative approach using SWOT analysis. The results show that sustainable tourism development in Jatiluwih Tourism Village emphasizes participatory, collaborative, and local wisdom–based approaches. Local community involvement plays a crucial role in the success of tourism management, although it remains at a moderate level of participation. The development of the village has produced positive impacts on economic, social, cultural, and environmental aspects, yet challenges such as waste management and land-use conversion still require serious attention. The recommended strategy is based on local wisdom and multi-stakeholder collaboration using the Strength–Opportunity (SO) approach, focusing on the village’s rice field landscape and cultural heritage as key attractions for educational and ecotourism development, promoting more equitable economic benefits.